Health-care-seeking behaviour in patients with hypertension: experience from a dedicated hypertension centre in Bangladesh - Mohammad Jahid Hasan; Md Zakir Hossain; Md Anwar Hossain; Koustuv Dalal; Md Abdul Baset; Probal Sutradhar; Mahabubul Alam; Tamanna Tabassum; Jannatul Fardous; Paramita Zaman; Md Abdur Rafi; Md Abdullah Saeed Khan; et al. (Blood Pressure)
Objective: The study aimed to assess health-seeking behaviour (HSB) and associated factors among hypertensive patients in Bangladesh.Methods: This cross-sectional study was conducted in the Hypertension & Research Centre, Rangpur, Bangladesh, between January 2022 and June 2022. A total of 497 hypertensive adults were recruited consecutively. A pre-tested structured questionnaire was deployed by the research team for data collection. Multivariable logistic regression analysis was used to explore the predictors of HSB.Results: The mean age of the hypertensive patients was 52 ± 11 (SD) years. Most of them were aged between 51 and 60 years (33%), female (55%), came from rural areas (57%), and belonged to middle socioeconomic class (68%). One-fourth of the patients (27%) had chosen informal healthcare providers for their first consultation. Fear of stroke (244, 45%), headache (170, 36%), and neck pain (81, 17%) were the three most common compelling causes of their visit to the hypertension centre. Age (aOR 0.78, 95% CI 0.68 − 0.89), male sex (aOR: 1.79, 95% CI 1.05 − 3.10), living in semi-urban (aOR 4.68, 95% CI 1.45 − 15.10) and rural area (aOR 1.68, 95% CI 1.01 − 2.80), farmers as occupation (aOR: 3.24, 95%CI: 1.31 − 8.06) and belonging to lower social economic class (aOR 4.24, 95% CI 1.68 − 10.69) were predictors of visiting informal providers of hypertensive patient. One-fourth of the hypertensive patients received consultation from informal healthcare providers.Conclusions: Raising awareness among patients and proper referral to specialised hypertension centres could promulgate the patients towards appropriate behaviour.